Ord, steder og andre ting vi tabte i krigen: om redactions - Bjering, Jens Christian Borrebye (Passage - Tidsskrift for litteratur og kritik, 2018)
Jens Bjering: “Words, Places, and Other Things We Lost in the War: On Redactions” The article investigates the use of government redactions in three texts which relate in different ways to the War on Terror: Ex-CIA agent Valerie Plame’s Fair Game, the Senate Select Committee on Intelligence’s Study of the Central Intelligence Agency’s Detention and Interrogation Program, and Mohamedou Ould Slahi’s Guantanamo Diary. While the formal reason for redacting texts is to prevent specific pieces of sensitive information from reaching the public, the article claims—and supports through its readings—that redactions in these cases also are used as literary-narrative strategies with which to frame the reader’s general reading experience and thus his or her overall impression of and opinion about the War on Terror.